Laboratory Experiment For Subject Ecology Of Production: Influence Of Water Vapour On The Amount Of Incident Sunlight - Balcárková, Lucie (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2019)
Electromagnetic radiation coming from the Sun passes through the Atmosphere. Part of the radiation is absorbed, another part is reflected back to the Space. This laboratory experiment was created to provide students a measurable proof of influence of water vapour to incident radiation.
Keywords: laboratory experiment; ecology of production; water vapour; electromagnetic radiation